Eficiência energética aplicada à instituição religiosa no município de Mossoró-RN - Almeida, Lucas Duarte de (Universidade Federal Rural do Semi-Árido, 2019)
The main purpose of this paper consists in proposing actions to be adopted to improve the level of energy efficiency and the quality of electric power in the building of the Religious Institution Igreja Matriz de São José located in the county of Mossoró, Rio Grande do Norte, with the main objective of reducing financial and environmental costs. First, measurements of illuminance’s levels, build areas and indexes of energy quality were permformed, as well as the data acquisition related to the installed load and the Institution’s consume profile. Thus during the work was realized that some systems do not conform to norms and standards, which motivated the elaboration of corrective projects for these systems. By possession of the data obtained through the measurements, these were analyzed through softwares: of lighting design, with the purpose of correction of the lighting systems; spreadsheets, for cost-benefit analyzes related to the proposed changes; and graphical data analysis, for the graphical visualization of the electric power quality’s indexes. About the energy quality indicators, it was noticed that the Institution presents specific problems that can be corrected in order to install a harmonic filter or even a bank of capacitors, but more extensive measurements are needed for the correct determination of this correction. Finally, the systems were classified according to their level of energy efficiency using the method established in the Technical Regulation of Quality for the Energy Efficiency Level of Commercial Buildings, Services and Public Buildings (RTQ-C).
Monografia
Keywords: Eficiência Energética; Qualidade de Energia; PBE; ENGENHARIAS::ENGENHARIA ELETRICA